Effect of light on structural properties and antioxidant activities of polysaccharides from soybean sprouts. Issue 7 (July 2015) - Yuan, Ming; Jia, Xuejing; Yang, Yong; Ding, Chunbang; Du, Lei; Yuan, Shu; Zhang, Zhongwei; Chen, Yanger
Graphical abstract